2015
DOI: 10.1111/jce.12649
|View full text |Cite
|
Sign up to set email alerts
|

Pouched Mitral Isthmus Is Associated with Incomplete Linear Block in Atrial Fibrillation Patients with Mechanical Mitral Valve Replacement

Abstract: Pouched MI accounts for the majority of AF patients with MMVR and may be associated with incomplete bidirectional linear block of MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Possible reasons: (1) The pouch structure existed in the isthmus of the mitral valve after valve replacement, which was the main reason affecting the MI linear block. Long et al and Deng et al 20,21 both reported that the isthmus of the mitral valve in patients with mechanical MVR may have pouched MI, which might result in significantly increasing the difficulty in the achievement of block across MI line. (2) Statistical Class II errors might be caused by the small sample size of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons: (1) The pouch structure existed in the isthmus of the mitral valve after valve replacement, which was the main reason affecting the MI linear block. Long et al and Deng et al 20,21 both reported that the isthmus of the mitral valve in patients with mechanical MVR may have pouched MI, which might result in significantly increasing the difficulty in the achievement of block across MI line. (2) Statistical Class II errors might be caused by the small sample size of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ideal site of balloon occlusion should be as proximal as possible to the juncture of VOM with CS, in order to achieve a larger intervention area, covering the connections between CS and LA (example.g., CS‐LAA connections). However, even with EIVOM, some patients with complex MI anatomy, such as those with mechanical mitral valve, 24 inherit pouch at the isthmus, the interposition of the circumflex artery in the vicinity of MI and the CS, or with a history of hypertrophic cardiomyopathy, are inevitably associated with a lower probability of achieving complete MI block.…”
Section: Discussionmentioning
confidence: 99%
“…As factors associated with a successful MI ablation, previous studies suggested the importance of the steerable sheath and contact force [ 17 ]. Anatomical factors such as the myocardial thickness and presence of pouches, length of the MI and distance to the LCX, high take off of the LIPV, and connection of the VOM have also been reported [ 25 28 ]. In this study, an interposition of the LCX was observed significantly more often in the group with an incomplete line of block.…”
Section: Discussionmentioning
confidence: 99%